ANALISIS KEBUTUHAN KARAKTER MAHASISWA PSIKOLOGI FAKULTAS ILMU SOSIAL DAN HUMANIORA UIN SUNAN KALIJAGA YOGYAKARTA - Palila, Sara (HUMANITAS, 2015)
AbstractThis study aims to find the characteristics that are needed by undergraduate students in Psycholocology under the Faculty of Social Sciences and Humanities Univeritas Islam Negri (UIN) Sunan Kalijaga Yogyakarta. Qualitative approach was used in this study. Data were obtained through interviews and FGD (Focused Group Discussion) with 38 students, five lecturers in which two of them are administrators of study program. The data was analyzed through some steps, which are data organization, data reduction on unit analysis, coding and interpretation. The results showed that three principal characters are needed by students: persistence, self-regulation, and empathy. These principal character appears in many forms derived characters. Characters derived from the persistence of the most widely appeared among others are disciplined, proactive, responsibility, consistent, and enthusiasm / passion. Characters derived from self-regulation appears most among others are optimistic, confident, tough, resilient, and positive thinking. While the derivative character of empathy most emerging among others are working together, to appreciate and respect others, listen and understand others.Key Words : emphaty, persistence, students’ characteristic, self regulation